Design of efficient implementation of II/4 DQPSK modulation for multipath fading channels - Hamdan, Fakhrul Radzy (2005)
This project will be base on the wireless communication using p/4 Differential Quadrature Phase Keying (p/4 DQPSK) modulation technique in the transceiver system. This modulation technique will be evaluated using the channel with the present of Additive White Gaussian Noise (AWGN) and multipath Rayleigh fading. The design of the system will be totally base on simulation. In this case the simulation tool MATLAB will be used. In this project, normal receiver structure for p/4 DQPSK was redesign by using multiplier-less method. The new receiver was designed to obtain simpler structure in term of hardware implementation where it able to reduce number of Integrated Circuit (IC) used in the design. Performance of the new receiver structure then will be evaluate base on the error performance of the system. In this case, relation of Bit-Error-Rate (BER) and Signal to Noise Ration (SNR) will be used to produce the result of error performance. Normal and new receiver structures which were design in p/4 DQPSK system will be study base on error performance and hardware complexity to obtain the most efficient result for the communication system.